Functional brain imaging in larval zebrafish for characterising the effects of seizurogenic compounds acting via a range of pharmacological mechanisms. (5th May 2021) - Winter, Matthew J.; Pinion, Joseph; Tochwin, Anna; Takesono, Aya; Ball, Jonathan S.; Grabowski, Piotr; Metz, Jeremy; Trznadel, Maciej; Tse, Karen; Redfern, Will S.; Hetheridge, Malcolm J.; Goodfellow, Marc; et al.
Abstract : Background and Purpose: Functional brain imaging using genetically encoded Ca 2+ sensors in larval zebrafish is being developed for studying seizures and epilepsy as a more ethical alternative to rodent models. Despite this, few data have been generated on pharmacological mechanisms of action other than GABAA antagonism. Assessing larval responsiveness across multiple mechanisms is vital to test the translational power of this approach, as well as assessing its validity for detecting unwanted drug‐induced seizures and testing antiepileptic drug efficacy. Experimental Approach: Using light‐sheet imaging, we systematically analysed the responsiveness of 4 days post fertilisation (dpf; which are not considered protected under European animal experiment legislation) transgenic larval zebrafish to treatment with 57 compounds spanning more than 12 drug classes with a link to seizure generation in mammals, alongside eight compounds with no such link. Key Results: We show 4dpf zebrafish are responsive to a wide range of mechanisms implicated in seizure generation, with cerebellar circuitry activated regardless of the initiating pharmacology. Analysis of functional connectivity revealed compounds targeting cholinergic and monoaminergic reuptake, in particular, showed phenotypic consistency broadly mapping onto what is known about neurotransmitter‐specific circuitry in the larval zebrafish brain. Many seizure‐associated compounds also exhibited altered whole brain functional connectivity compared with controls. Conclusions and Implications: This work represents a significant step forward in understanding the translational power of 4dpf larval zebrafish for use in neuropharmacological studies and for studying the events driving transition from small‐scale pharmacological activation of local circuits, to the large network‐wide abnormal synchronous activity associated with seizures.